Prevalência de Síndrome de Burnout e fatores associados ao trabalho entre bombeiros militares do estado do Ceará - Carvalho, Thalyta Gleyane Silva de (2020)
The firefighter profession is considered one of the most demanding professions, due to the nature of their functions and situations experienced. These situations, due to their frequency, are eventually inducers of high levels of stress and, when continued, without adequate coping strategies, can lead to burnout syndrome. The present study aimed to estimate the prevalence and analyze possible associations between burnout syndrome, occupational stress and organizational factors of work in Military Firefighters of Fortaleza-Ceará. This is a cross-sectional study conducted in 2019 (June to August), with CBMCE military firefighters in the Operational and Administrative Units distributed in the city of Fortaleza, in the state of Ceará. The study participants totaled 363 male military firefighters, recruited using stratified random sampling. After informed consent, the information was obtained through a self-administered questionnaire, containing sociodemographic, organizational, occupational stress, and Burnout syndrome information. Logistic regression models were used to study the independent association between sociodemographic characteristics, occupational stressors and burnout syndrome (total and its separate dimensions). The prevalence of total burnout syndrome was 4.8%. When analyzing the dimensions of BS separately, we observed that they have a higher prevalence than the final outcome, where emotional exhaustion had a prevalence of 21.81%, depersonalization of 20.88% and low professional achievement of 25.98%. In the multivariate model, military firefighters with high professional wear were more likely (OR: 5.46, 95% CI: 1.11- 26.89) to develop Burnout Syndrome; those with high demand at work had more Emotional Exhaustion (OR: 5.77; 95% CI: 3.14-10.57) and Depersonalization (OR: 3.17; 95% CI: 1.81-5.55). Only professionals with low control at work (OR: 2.30; 95% CI: 1.33 - 3.96) obtained a statistically significant association for Low Professional Achievement. We conclude that there is a statistical association between burnout syndrome, occupational stress and organizational factors in the work of Military Firefighters in the State of Ceará.